DEVELOPING INTERCULTURAL-BASED SPEAKING MATERIALS FOR THE 9TH GRADE STUDENTS OF JUNIOR HIGH SCHOOLS TO PRACTICE LINGUISTIC FEATURES AND PEACE EDUCATION IN KURIKULUM MERDEKA - Waisya, I Gede Komang Waisya Giri Wisnawa; Budiarta, Luh GD Rahayu (Undiksha Press, 2024)
This research focuses on developing speaking materials based on intercultural themes for 9th-grade junior high school students, in accordance with the Merdeka Curriculum. The goal is to integrate intercultural competence and peace education while enhancing students' speaking skills. The study utilized the Successive Approximation Model (SAM) for the development of these materials, which involved surveys, document analysis, and expert evaluations. Findings indicated that students have a strong preference for speaking activities that are engaging, interactive, and culturally relevant. The materials were revised multiple times in response to expert feedback, ensuring alignment with the Merdeka Curriculum's objectives of promoting inclusivity, critical thinking, and effective communication skills. The final version comprises activities designed not only to enhance linguistic abilities but also to foster cultural awareness and peacebuilding.